PERAN MANAJER DALAM PEMBINAAN ETIKA PERAWAT PELAKSANA DALAM PENINGKATAN KUALITAS PELAYANAN ASUHAN KEPERAWATAN - Roymond H. Simamora (Jurnal Ilmu Kesehatan Masyarakat, 2008)
Construction constitutes an effort to fix and increases science, skill, attitude or personality characters. In do manner construction a hall head shall can do approaching and understands nurse characteristic that will at build, so gets to apply construction method suitably so effort that doing to result optimal result. Besides executor nurse in each construction process phase of planning, performing and evaluation constitutes an important thing to be noticed collaboration interlaces that since early, so construction process walks smoothly. This research utilize qualitative approaching that aims to give construction picture of hall head to executor nurse manner that becomes to take on answer him in service to care, on a more special figures to process construction of planning, performing and its evaluation. Collecting data is done through visceral interview( indepth interview ). This observational respondent consisting of four hall head of nurse room lodge hospital that is at Jember city, and three executor nurse of each hall that carry the wind its hall become respondent in observational it so its amount available 12 person. Result observational to point out that planning constitutes a necessary for thing hall head before performs construction. Better hall head sits with talk about nurse manner construction that effective, mutually commutes experience or concept even in build. In each phase of advisable construction process with nurse that is built of since first few so most composes collaboration and positive commitment. On manner construction process is required marks sense special default about manner construction that cans be base and referenced to prevent incorrect perception and prevents subjective manager to employee. Keywords: Manager role, Nurse Manner, Nursing Care quality